Neuropathological Aspects of SARS-CoV-2 Infection: Significance for Both Alzheimer’s and Parkinson’s Disease - Silva, Jaime; Patricio, Felipe; Patricio-Martínez, Aleidy; Santos-López, Gerardo; Cedillo, Lilia; Tizabi, Yousef; Limón, Ilhuicamina Daniel (Frontiers in Neuroscience, 2022)
Evidence suggests that SARS-CoV-2 entry into the central nervous system can result in neurological and/or neurodegenerative diseases. In this review, routes of SARS-Cov-2 entry into the brain via neuroinvasive pathways such as transcribrial, ocular surface or hematogenous system are discussed. It is argued that SARS-Cov-2-induced cytokine storm, neuroinflammation and oxidative stress increase the risk of developing neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease. Further studies on the effects of SARS-CoV-2 and its variants on protein aggregation, glia or microglia activation and blood-brain barrier are warranted.